HUBUNGAN DAYA TAHAN JANTUNG PARU DENGAN KETERAMPILAN BERMAIN FUTSAL PADA KLUB SATOE ATJEH FUTSAL ACADEMY - Zulheri Is; Septi Hariansyah (Program Studi Pendidikan Jasmani, FKIP Universitas Bina Bangsa Getsempena, 2020)
Futsal is a team sport played by 2 teams of 5 people per team with details of 1 goalkeeper and 4 attacking players. The purpose of this game is to put the opponent's kegawang ball in, and against the opponent put the ball into his own goal. Based on the background of the problem formulated by the author,